Analisis Pelanggaran Etika dan Hukum Bisnis dalam Perdagangan Pakaian Bekas Impor Ilegal - Anastasya Salsabila Alika Putri; Halimah Zahrah; Azmi Aufal Marom; Shahnaz Rahmadina Nurhidayat (Teewan Journal Solutions, 2025)
This research aims to analyze ethical and legal violations in the trade of illegal imported second-hand clothing in Indonesia, which involves practices that harm consumers and the local industry. This research uses a literature study method by reviewing 16 national journals related to business ethics, business law, and their impact on society and the economy. The research results show that ethical and legal violations occur in the form of lack of transparency, brand counterfeiting, tax evasion, and negative impacts on the local textile market. The recommendations provided include the need for strengthening law enforcement, stricter regulations, and education for the public and business actors to combat these illegal practices